Max found two sticks - Pinkney, J. Brian (Simon & Schuster Books for Young Readers, 1994)
Although he doesn't feel like talking, a young boy responds to questions by drumming on various objects, including a bucket, hat boxes, and garbage cans, echoing the city sounds around him.